Forest gardens management under traditional ecological knowledge in West Kalimantan, Indonesia - BUDI WINARNI; ABUBAKAR M. LAHJIE; B.D.A.S. SIMARANGKIR; SYAHRIR YUSUF; YOSEP RUSLIM (Biodiversitas Journal of Biological Diversity, 2018)
Winarni B, Lahjie AM, Simarangkir B.D.A.S., Yusuf S, Ruslim Y. 2018. Forest gardens management under traditional ecological knowledge in West Kalimantan, Indonesia. Biodiversitas 19: 77-84. Local wisdom of Dayak Kodatn people in West Kalimantan in forest management shows that human and nature are in one beneficial ecological unity known as Traditional Ecological Knowledge (TEK). Former cultivation forest areas are managed in various ways, including planting forest trees, fruit-producing plants, and rubber trees until they transform into the forest garden. This research used three models, monoculture rubber cultivation (Model 1), combined rubber and camphor cultivation (Model 2), and combined rubber and durian cultivation (Model 3). This research intended to: (i) analyze the production of rubber latex and durian fruit; (ii) analyze the growth increment of camphor and durian trees; (iii) analyze the financial feasibility of rubber tree plantation, combined rubber and camphor tree plantation, and combined rubber and durian trees plantation; (iv) formulate the model of rubber cultivation. This research also used measurement methods other than field measurement, which were tree diameter and height, rubber latex and durian fruit weight, and questionnaire interviews. The maximum productions of rubber latex from three models were achieved at the age of 17 years, while maximum production of durian fruits was achieved at the age of 55 years. The maximum growth increment of camphor and durian trees were achieved at the age of 40 years. Based on NPV analysis and IRR, those three models were worthy of being cultivated. Financially, the combined rubber and durian cultivation (Model 3) was the most profitable, followed by monoculture rubber cultivation (Model 1), and lastly the combined rubber and camphor cultivation (Model 2).